KOMBINASI SARINGAN PASIR LAMBAT DALAM PENURUNAN KADAR Fe(BESI) AIR SUMUR GALI MASYARAKAT DIWILAYAH KERJA PUSKESMAS LASIKABUPATEN AGAM - Fatma, Fitria (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The puskesmas lasi having 3 the nagari usually have around , namely the nagarilasi , bukik batabuah , and canduang the koto .The number of or dug wells who 2754 wellnear the village of with the total number of of jorong a the name that was most often areJorong Bingkudu.Any water content or dug wells nagari bingkudu the majority ofcontaining iron ( fe ) as much as 54 % .The nature of all that fe higher than thestandardization of quality standards of the water may cause some serious problems todaythe environment and health.The nature of all that fe or dug wells the community inKenagarian lasi as much as 2,05 mg / l in the year 2014 , the nature of all that fe 2,09 mg /l years 2015, and the nature of all that fe 2,89 mg / l years 2016.This study aims to toinvestigate the extent to a combination of a sieve sand slow with the media sand of thezeolite, charcoal hand across his, sand and gravel.In a reduction of the nature of all thatsubstance as iron ( fe ) water from the wells dug out of the people by keeping the use of asieve sand slow in the work area of the PuskesmasLasi Kabupaten Agam years2017.Where is this report is written with two types of the test and been approved treatmentpt pgn promised to supply a sieve 1 with medium sand of the zeolite 10 police post cmgrand cinema, charcoal hand across his 10 police post cm grand cinema, sand 3 cm keikil2 cm and sifting the 2 with medium sand of the zeolite 40 police post cm grand cinema,charcoal hand across his 15 police post cm grand cinema, sand 4 police post cm grandcinema, gravel 3 police post cm grand cinema.Based on the research be made known bethat the level of substance as iron ( fe ) in water or dug wells is 3,72 mg / l, after filteringthese chareges in the future 1 rata-rata 0.7512 mg /l , and after sifting 2 is 0.4450 mg / l.With pvalue 0,007.There are differences between the research rata-rata filtered by sifting firts.Thismeans that the combination is more effective than filtering filtering two with combinationsof filtering media sand of the zeolite 40 cm, charcoal hand across 15 cm, sand 4 cm, gravel3 cm .Keywords: Slow sand filter, zeolite sand, shell charcoal, sand, Gravel,iron content (fe)